2020
DOI: 10.18699/vj20.663
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional features of phytoene synthase isoforms PSY1 and PSY2 in pepper Capsicum annuum L. cultivars

Abstract: The fruits of various pepper cultivars are characterized by a different colour, which is determined by the pigment ratio; carotenoids dominate in ripe fruits, while chlorophylls, in immature fruits. A key regulator of carotenoid biosynthesis is the phytoene synthase encoded by the PSY gene. The Capsicum annuum genome contains two isoforms of this enzyme, localized in leaf (PSY2) and fruit (PSY1) plastids. In this work, the complete PSY1 and PSY2 genes were identified in nine C. annuum cultivars, which differ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Its level of expression was highest in cotyledons and lowest in the pericarp. It was detected not only in the leaves and immature fruit but also in mature fruit [ 44 ]. Some studies also found that Psy2 could compensate for the loss of Psy1 in pepper fruit [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its level of expression was highest in cotyledons and lowest in the pericarp. It was detected not only in the leaves and immature fruit but also in mature fruit [ 44 ]. Some studies also found that Psy2 could compensate for the loss of Psy1 in pepper fruit [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, C. annuum has hundreds of varieties and, among other characteristics, two large groups can be made sweet and spicy according to the content of capsaicin (Vázquez-Espinosa et al 2020 ). On the contrary, the ripening process of pepper fruits involves many changes at the phenotypic, transcriptomic, proteomic, and metabolomic levels, and its big genome size, in comparison to other Solanaceae, makes its analysis complex (Dyachenko et al 2020 ; Razo-Mendivil et al 2021 ; Esposito et al 2022 ; Kovács et al 2022 ; Del Giúdice et al 2023 ). Recently, “omic” approaches have been carried out to study specific aspects of the ripening process (Chiaiese et al 2019 ; Dubey et al 2019 ; Zuo et al 2019 ; Lopez-Ortiz et al 2021 ; Rödiger et al 2021 ; Momo et al 2022 ; Villa-Rivera et al 2022 ; Song et al 2022 ; Liu et al 2023 ; Wang et al 2024 ) which are dependent on the variety, environmental growth conditions, fruit position, and ripening stage (Ribes-Moya et al 2020 ; Jang et al 2022 ; Lahbib et al 2023 ; Guijarro-Real et al 2023 ; Islam et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Car coordinates with Chl in chloroplasts and is an important component in photosynthetic organs and photoprotective systems [ 31 ]. Car accumulates in plastids and forms different colors in plants [ 32 35 ], such as orange, yellow or red [ 36 ]. The Chl and Car contents and the total Chl/Car ratio of LT leaves were lower than NT at the same period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PSY and PDS are key enzymes in Car biosynthesis [ 37 , 38 ]. The mutation of PSY and PDS can cause the decrease of carotenoid content [ 32 , 39 , 40 ]. In our study, the expression levels of PSY and PDS were significantly decreased under LT, which can explain the yellow leaves under LT.…”
Section: Discussionmentioning
confidence: 99%